Methyl jasmonate enhanced production of rosmarinic acid in cell cultures of Satureja khuzistanica in a bioreactor. Issue 8 (8th June 2016) - Khojasteh, Abbas; Mirjalili, Mohammad Hossein; Palazon, Javier; Eibl, Regine; Cusido, Rosa M.
Abstract : The growing interest in rosmarinic acid (RA), an ester of caffeic acid and 3, 4‐dihydroxyphenyl lactic acid, is due to its biological activities, which include cognitive‐enhancing effects, slowing the development of Alzheimer's disease, cancer chemoprotection, and anti‐inflammatory activity. Inspired by the challenge of meeting the growing demand for this plant secondary metabolite, we developed a biotechnological platform based on cell suspension cultures of Satureja khuzistanica . The high amounts of RA produced by this system accumulated mainly inside the cells. To further improve production, two elicitors, 100 μM methyl jasmonate (MeJA) and 40 mM cyclodextrin (CD), were tested, separately and together. MeJA increased RA productivity more than 3‐fold, the elicited cultures achieving an RA production of 3.9 g L −1 without affecting biomass productivity. CD did not have a clear effect on RA production, and under the combined treatment of MeJA + CD only a small amount of RA was released to the medium. When the cell culture was transferred from a shake flask to a wave‐mixed bioreactor, a maximum RA production of 3.1 g L −1 and biomass productivity of 18.7 g L −1 d −1 was achieved under MeJA elicitation, demonstrating the suitability of S. khuzistanica cell suspensions for the biotechnological production of this bioactive plant secondary metabolite.